O INSTITUTO DA TRANSAÇÃO PENAL E A EFETIVIDADE DE SEU CUMPRIMENTO NO JUIZADO ESPECIAL CRIMINAL DE IMPERATRIZ-MA - CARVALHO, Gleidysson José Brito de (2016)
This paper attempts to analyze the effectiveness of the enforcement of the criminal transaction institute in the Special Criminal Court Imperatriz-MA. Therefore, we seek to make an analysis of the historical context in which it gave the appearance of Law No. 9,099 / 95, the inaugural consensual justice in the Brazilian criminal law, as well as a study of the main principles underlying the functioning of the Courts. He studied the institution of criminal transaction in a more detailed way, trying to conceptualize it and indicate some foreign institutes that served him for inspiration. It is also its legal nature, is mere discretion of the prosecution, or subjective right of the accused. At the end, we analyze data collected about compliance with the criminal transaction agreements indicated locus. It was used for quantitative and qualitative research, mainly based on literature review and case study.